Sifat Fisik Daging Sapi, Kerbau dan Domba pada Lama Postmortem yang Berbeda (Physical Characteristics of Beef, Buffalo and Lamb Meat on Different Postmortem Periods) - Komariah (Komariah); Sri Rahayu; Sarjito (Sarjito) (Faculty of Animal Science, Universitas Gadjah Mada, 2009)
Physical characteristic of meat is very important in processing since it will determine the quality and type of processing being made. Meat characteristics of each livestock may different, but it is thought to be the same. Society in general assess the characteristics of buffalo and lamb meat with reference to the characteristics of beef, so that the processing of meat into processed meat products often have different outcomes. The aim of the experiment was to studythe physical characteristic (pH, water holding capasity, tenderness, and cooking loss) of beef, buffalo meat and lamb kept at the different by postmortem periods. The design used in experiment was a completely randomized design withfactorial pattern 2x3. The treatments were was postmortem periods (4 and 6 hours) and difference in kind of meat (beef, buffalo meat and lamb). The data was analysed by analysis of variance, and continued by Tukey test forsignificant value. The results showed that the kind of meat had a significant effect (P<0.05) on pH, water holding capacity, tenderness and cooking loss, while postmortem had significant effect (P<0.05) on pH and water holdingcapacity. The mean pH value of buffalo meat (6.05±0.36) was significantly (P<0.05) higher than pH value of beef (5.70±0.20) and lamb (5.99±0.11). The mean water holding capacity of beef was significantly (P<0.05) higher thanbuffalo meat and lamb. The mean shear force of beef (6.73±0.16 kg/cm2) and buffalo meat (6.53±0.38 kg/cm2) were significantly (P<0.05) higher than lamb (5.24±0.93 kg/cm2).(Key words: Physical characteristic, Postmortem, Beef, Buffalo, and Lamb meat)